Experimental studies on evaporation kinetics of gold nanofluid droplets: Influence of nanoparticle sizes and coating on thermal performance. (25th January 2021) - Zaaroura, Ibrahim; Harmand, Souad; Carlier, Julien; Toubal, Malika; Fasquelle, Aurélie; Nongaillard, Bertrand
Highlights: Gold nanofluid droplets evaporation heated by silicon substrate is studied. Gold nanofluid has a better evaporation rate compared to pure water. Impact of particle sizes and coating on the behavior of mass heat transfer. Nanoparticles stability effect on the thermal Marangoni lifetime. Stability effect on the droplet evaporation rate is important. Abstract: In this work, a series of experiments investigate the evaporation of gold nanofluid sessile droplets on a perfluorodecyltrichlorosilane (PFTS) silicon substrate heated to 77 °C. The evaporation processes of different nanofluid droplets of the same initial volume, all for a 1% Cv volume concentration prepared from the 0.1 mM original suspension, are visualized to examine the size effect of gold nanoparticles (2.2, 5 and 10 nm) and the impact of surface coating (with and without Citrate capping in phosphate-buffered saline solvent) on enhancing heat transfer. This study open access to understand the size effect of gold nanoparticle in very small scale and the different types of surfactant on heat and mass transfer during the evaporation of droplet. Two methods are used to analyze the evaporation process, an optical one coupled to an infrared thermography method and an acoustic method. These complementary methods have the ability to investigate clearly the solid/liquid and liquid/vapor interfaces at the same time. From the optical observation, using a Drop Shape Analyzer (Kruss system), the evolution in time of the shape of the droplets (contact angle, base diameter and volume) are measured under controlled conditions (Humidity = 50%, Tatm = 23 °C). Then, the evaporation rate is deduced from the measurements of the evolution of volume in time. At the same time, an infrared camera is used to observe the droplet surface gradient temperature, air/liquid interface, due to thermal Marangoni flow. The acoustic method, based on a high- frequency echography principle, allowed to monitor the stability of nanoparticles inside the droplets (Au-water mixture) during the process of evaporation. From the kinetics of the reflection coefficient at the interface of the silicon substrate over which the nanofluids are deposited, the results show that the evaporation rate of 5 nm Au-water mixture (phosphate buffered saline solvent only) was faster than that of 10 nm Au-water mixture. While with citrate capping-PBS, the evaporation rate of the largest particle sizes (10 nm Au-water mixture) was the fastest than that of the smaller sizes (2.2 and 5 nm). Also, the 5 nm gold nanofluids with PBS showed the highest evaporation rate (+35%) than that of citrate capping gold nanofluids (+15%). As results, the addition of a surfactant (citrate capping) decreases the effectiveness of the heat transfer of gold nanofluids. This seems to be due to the absence of Marangoni cells in droplets made of Au-water mixtures (Citrate capping-PBS). Moreover, reducing in the thermal conductivity of gold nanofluid due to the surfactant coating by covering the gold nanoparticles surface and this eventually affected the nanofluid thermal properties. This is further supported by the acoustic method, which clearly shows worse stability of the nanoparticles in the latter case.